The association between stent design and patient exercise intensity: structural coupling effects and hemodynamic analysis - Lv, Rui; Li, Daochun; Zhao, Shiwei; Shu, Peng; Xiang, Jinwu (Frontiers in Bioengineering and Biotechnology, 2024)
IntroductionIn-stent restenosis remains a significant challenge in coronary artery interventions. This study aims to explore the relationship between exercise intensity and stent design, focusing on the coupled response of the stent structure and hemodynamics at different exercise intensities.MethodsA coupled balloon-stent-plaque-artery model and a fluid domain model reflecting structural deformation were developed to investigate the interaction between coronary stents and stenotic vessels, as well as their impact on hemodynamics. The study examines the influence of stent connectors on the mechanical response of both the plaque and the coronary artery, with hemodynamic analyses conducted under three exercise intensities: rest, moderate exertion, and maximal exertion.ResultsThe model effectively simulates the gradual expansion of the stent, plaque, and artery, as well as the recoil behavior post-expansion. The gradual adaptation of the stent to the plaque during the initial expansion phase helps mitigate the adverse effects of the dog-boning phenomenon. Areas of low time-averaged wall shear stress (TAWSS) and high relative residence time (RRT) are observed at both ends and near the stent, with a general decreasing trend as exercise intensity increases. Additionally, the study quantifies the changes in hemodynamic characteristics across different physiological states. Specifically, the areas of low TAWSS and high RRT are significantly reduced during moderate exertion, with no further substantial reduction observed at maximal exertion.DiscussionThese findings provide valuable insights for the design of stent connectors and offer guidance on optimal exercise intensity for patients undergoing stent interventions. Future research, combining dynamic vascular wall deformation and advanced imaging techniques, could lead to more precise and effective stent designs tailored to individual patients.